2004
DOI: 10.1021/ma0359988
|View full text |Cite
|
Sign up to set email alerts
|

Highly Softened Polyurethane Elastomer Synthesized with Novel 1,2-Bis(isocyanate)ethoxyethane

Abstract: A novel diisocyanate, 1,2-bis(isocyanate)ethoxyethane (TEGDI), whose backbone is ether bonds was used for the preparation of polyurethane elastomers (PUEs). 1,6-Hexamethylene diisocyanate (HDI) was also used as a control. The PUEs were prepared with either TEGDI or HDI, poly-(oxytetramethylene) glycol (PTMG), and curing agent by a prepolymer method. Differential scanning calorimetry, infrared spectroscopy, and wide-angle X-ray diffraction revealed that the phase separation of the network TEGDI-based PUEs was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
93
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 10 publications
0
93
0
1
Order By: Relevance
“…To form the microphaseseparated structure in polymers, they need to possess block structures, which are chemically connected each other. It is well-known that the polyurethane elastomers (PUEs), which possess the multiblock structure, show the microphase-separated structure, [1][2][3][4][5][6] resulting in giving some unique properties, such as mechanical and adhesive properties [6][7][8][9][10][11][12][13][14][15][16] and biocompatibility. 17 To functionalize the PUs with the microphase-separated structure, one needs to control the structures precisely.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To form the microphaseseparated structure in polymers, they need to possess block structures, which are chemically connected each other. It is well-known that the polyurethane elastomers (PUEs), which possess the multiblock structure, show the microphase-separated structure, [1][2][3][4][5][6] resulting in giving some unique properties, such as mechanical and adhesive properties [6][7][8][9][10][11][12][13][14][15][16] and biocompatibility. 17 To functionalize the PUs with the microphase-separated structure, one needs to control the structures precisely.…”
mentioning
confidence: 99%
“…There has been reported some factors to control the microphaseseparated structure. A polymerization method, 13 thermal treatment 3,14 and chemical structures of raw materials including molecular weight [6][7][8][9][10][11][12]15,16 can be given as examples. First, by changing the polymerization method, one can control the primary structure of the PUs.…”
mentioning
confidence: 99%
“…The soft segment can be classified as an ether or ester series, including the carbonate ones. 7,8 Studies have been reported with polyamide in the thermoplastic elastomers or rubbers as blends. 9 The PA 6/acrylonitrile-butadiene-styrene blends obtained with an imidized acrylic polymer as a compatabilizer revealed supertough properties over a wide range of component proportions.…”
mentioning
confidence: 99%
“…Poly(oxytetramethylene) glycol (PTMG: M n ¼ 2000, Asahikasei Chemicals Co., Ltd., Japan), 4,4 0 -diphenylmethane diisocyanate (MDI, Nippon Polyurethane Industry Co., Ltd., Japan) and 1,4-butandiol (BD) and 1,1,1-trimethylol propane (TMP, Wako Chemicals Co., Ltd., Japan) were used. The curing agents used to control the microphase separation were BD, TMP and a mixture of BD plus TMP at weight ratio of 75/25.…”
Section: Experimental Part Materialsmentioning
confidence: 99%